2020
DOI: 10.1101/2020.11.25.398131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automatic identification of bird females using egg phenotype

Abstract: Identification of individuals greatly contributes to understanding animal ecology and evolution, and in many cases can only be achieved using expensive and invasive techniques. Advances in computing technology offer alternative cost-effective techniques which are less invasive and can discriminate between individuals based on visual and/or acoustic cues. Here, we employ human assessment and an automatic analytical approach to predict the identity of common cuckoo (Cuculus canorus) females based on the appearan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 82 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…In both Common Moorhens and King Rails, a high degree of phenotypic overlap in egg pattern among clutches laid by different females made discrimination of clutches difficult. Eggs laid by different female Common Cuckoos similarly showed a high degree of phenotypic overlap and were also difficult to classify using automatic clustering methods, such as random forest analysis, or human assessment [ 29 ]. Better success in discriminating eggs has been demonstrated in species under strong selection for egg recognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In both Common Moorhens and King Rails, a high degree of phenotypic overlap in egg pattern among clutches laid by different females made discrimination of clutches difficult. Eggs laid by different female Common Cuckoos similarly showed a high degree of phenotypic overlap and were also difficult to classify using automatic clustering methods, such as random forest analysis, or human assessment [ 29 ]. Better success in discriminating eggs has been demonstrated in species under strong selection for egg recognition.…”
Section: Discussionmentioning
confidence: 99%
“…They found that when fewer variables were included correct egg classification decreased, suggesting that multiple eggshell characteristics are used by birds for egg recognition. Due to how the vertebrate visual cortex processes all aspects of egg variation simultaneously, humans may be better at visually discriminating eggs than any program currently available (though opinions on this differ [ 29 , 48 , 51 ]). Nevertheless, we were able to use matching output from NPM in combination with spatial and temporal data collected in the field to identify probable cases of parasitism and returning breeders that were previously undetected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spot density was determined for each egg by counting the number of distinct (i.e., human‐visibly disconnected) maculations along the long axis of the egg and dividing the resulting number by the length of that egg. We did not use digital data or other software‐based approaches to analyze eggshell maculation patterns in our study because none of the published spot‐based metrics are based, sensu stricto, on measurement‐driven avian visual‐physiology derived perceptual modeling (unlike coloration analyses, see below), despite their increasing use for such purposes (e.g., Stoddard et al., 2014, Gómez and Liñán‐Cembrano, 2016, Šulc et al, 2020).…”
Section: Methodsmentioning
confidence: 99%